Individual and work related factors associated with symptoms of musculoskeletal complaints. I. A quantitative registration system. Issue 3 (March 1992) - Westgaard, R H; Jansen, T
Abstract : A registration system for symptoms of occupational musculoskeletal injuries has been developed and evaluated. The system is based on the recording of two aspects of the pain sensation: the intensity (five point scale) and the frequency (three point scale) of pain. The two primary indicators are summed to give a combined symptom score. The scoring system was evaluated in terms of its ability to predict the probability of a medical consultation due to a musculoskeletal pain problem. The intensity and frequency parameters were shown to contribute significantly and to carry equal weight when optimising the symptom score by a logistic regression analysis. In the scoring of pain symptoms a distinction was made between pain experienced during and outside working hours and only the first category was included. The separation eliminated some symptoms that the workers did not consider work related (mostly due to migraine, arthritis). Repeated interviews of 14 subjects showed, however, that this procedure could cause classification problems.